Comparative Study Between Arthroereisis Versus Calcaneal Lengthening In Planovulgus Foot In Cerebral Palsy Children (Journal of Pharmaceutical Negative Results, 2023)
Background: Planovalgus deformity of the foot is common among cerebral palsy patients. There is no true consensus about the best way of treating this common deformity especially when surgical interference is required. Treatment options range from orthotics to complex surgical procedures.Patient and Methods: The current study is a randomized prospective comparative study designed to evaluate and compare the effectiveness of 2 different procedures in the correction of symptomatic flexible pes planovalgus in ambulatory CP patients by comparing the clinical outcomes, radiographic outcomes, patients (or parents) satisfaction and tolerance to shoes or braces 6 months after each procedure. The study was divided into 2 groups: Group 1: subtalar arthroereisis using the prostop screw technique was done for 18 feet in 9 cases, group 2: lateral column calcaneal lengthening using iliac bone graft was done for 18 feet in 11 cases.Results: There was a statistically significant improvement after both procedures in comparison to the preoperative parameters. No statistically significant differences were observed between the two groups regarding the aforementioned outcomes except for TNCA denoting more power of Evans osteotomy in the correction of forefoot abduction. In addition, neither procedure caused any loss of hindfoot mobility. Therefore, both procedures are valid options for the surgical management of PPV in ambulatory spastic CP patients.Conclusion: The study is designed to evaluate the power of correction of the symptomatic pes planovalgus in ambulatory spastic CP patients by subtalar arthroereisis (prostop technique) in comparison to lateral column calcaneal lengthening technique.